Consulting with Caregivers : Using Formative Research to Improve Maternal and Newborn Care and Infant and Young Child Feeding in the Lao People's Democratic Republic - Gillespie, Anna (World Bank, Washington, DC, 2013)
Improving maternal and newborn care and young child feeding will decrease under five mortality and malnutrition in developing countries. To help design interventions in these areas, a study was conducted in the Lao PDR. The study found that washing newborns after delivery and delaying breastfeeding for 1-3 days are common practices that may expose newborns to hypothermia. Few caregivers practice clean cord care and exclusive breastfeeding for the first six months, increasing the risk of infection. Most women deliver at home without assistance from a trained provider. They also restrict what they eat based on traditional beliefs about foods thought to affect mothers' health or breastmilk. Traditional beliefs also determine how young children are fed. Most caregivers, when asked to try four feeding recommendations for young children (add or give more animal food, increase the amount of food, number of feedings, and vegetables and fruits), were willing to try and continue them. Many caregivers were surprised about how much and what types of foods children can consume, if they are encouraged to, and valued receiving new information about how to improve young child feeding. The study conclusions are that newborn care can be improved using low-cost technologies such as keeping newborns warm by deferring washing for 24 hours, and wiping, wrapping and breastfeeding newborns immediately after delivery. Risk of infection can be reduced by proper care of the umbilical cord and by exclusively breastfeeding infants for six months. What women eat can be improved by promoting the consumption of certain foods that improve the quality and quantity of breastmilk. To improve the feeding of young children, messages are needed about how much and what types of foods they require and how to encourage them to eat those foods.